More than a Fence: (de)Constructing Mexico-U.S. Borders - Rivera, Kendra Dyanne; Rivera, CJ; Moss, Kristin; Chu, Melanie; Avalos, David; Calore, Pam; Fernandez, Maria Teresa
An Introduction to the Exhibit: From Kendra Dyanne Rivera, PhD This exhibit is a multi-media installation of photography, sculpture, and texts that explore the symbolic and experienced impact of the Mexico-U.S. Border. Created through a collaboration of CSUSM professors, students, and the community, this exhibit engages the audience by questioning the multiple and contested meanings of the borderlands and immigration. Not long after I began my ethnographic research with the U.S. Border Patrol, I realized something: Not many people actually know what the border looks like. They don't understand the experiences of those whose lives are impacted by "the fence." So when my son, CJ, got bored traveling to the border with me, I handed him a camera and he started taking pictures of the border. When I rode along with agents who worked "on the line," I continued to gather a photographic visual ethnography. Visual ethnography de-centers the written word as the primary source of knowledge and questions how we construct meanings based on the images we encounter. From 2007-2013, CJ and I created a visual ethnography of digital photography that allowed us to explore the border in ways that were otherwise challenging to articulate. The texts accompanying the photos in this exhibit offer some highlights from observations and interviews with Border Patrol agents during my research. When planning the exhibit, I felt we needed a collaboration that would reflect the experiences of those who seek to cross the border as well as those who patrol it. I sought out the expertise of Kristin Moss and Melanie Chu to help curate the exhibit. Soon thereafter, we invited Professor David Avalos, of the Visual and Performing Arts Department, to join us. He worked with students in the Spring 2013 Introduction to Sculpture class to create collaborative art works reflecting symbolic interpretations of the border. He then invited Pam Calore and Maria Teresa Fernandez, two artists who have documented the immediate impact of the border fence on human lives, to contribute sculpture and photographs. The Mexico-U.S. border and immigration policies do not occur in a vacuum; they rely on society's notions about immigrants, the "other," and the "American Dream." The border itself is not simply a geographic boundary between two countries; it is a visual and symbolic communication of the nation's sense of identity. The goal of this exhibit is to open a discussion about that identity. We hope that those who visit the exhibit will ask questions such as "Why do we need a fence?" "Who does the border fence and policy serve?" and "How might we re-vision a new type of border?" Many who visit the exhibit may have their own stories about crossing the border, working along the border, or visiting the border. You or someone you know may have been impacted by border or immigration policies, or you may have questions about what others' experiences are like. We invite you to share your story, leave a thought, prayer, or inquiry by adding to the "participation" section of the exhibit—the Border Fence Collaboration—located by the elevators.